2018
DOI: 10.3390/ijerph15102301
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training Attenuates Obesity-Induced Skeletal Muscle Remodeling and Mitochondria-Mediated Apoptosis in the Skeletal Muscle

Abstract: Obesity is characterized by the induction of skeletal muscle remodeling and mitochondria-mediated apoptosis. Exercise has been reported as a positive regulator of skeletal muscle remodeling and apoptosis. However, the effects of exercise on skeletal muscle remodeling and mitochondria-mediated apoptosis in obese skeletal muscles have not been clearly elucidated. Four-week-old C57BL/6 mice were randomly assigned into four groups: control (CON), control plus exercise (CON + EX), high-fat diet (HFD), and HFD plus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 41 publications
4
27
0
Order By: Relevance
“…Obesity is also characterized by the induction of skeletal muscle remodeling as well as mitochondria-mediated apoptosis (115). On the contrary, exercise has been reported as a positive regulator of skeletal muscle remodeling and apoptosis, however, as aforementioned, obese individuals typically present with low levels of physical activity (115).…”
Section: Implications Of Obesity For Aging Muscle Obesity and Musclementioning
confidence: 99%
See 1 more Smart Citation
“…Obesity is also characterized by the induction of skeletal muscle remodeling as well as mitochondria-mediated apoptosis (115). On the contrary, exercise has been reported as a positive regulator of skeletal muscle remodeling and apoptosis, however, as aforementioned, obese individuals typically present with low levels of physical activity (115).…”
Section: Implications Of Obesity For Aging Muscle Obesity and Musclementioning
confidence: 99%
“…Obesity is also characterized by the induction of skeletal muscle remodeling as well as mitochondria-mediated apoptosis (115). On the contrary, exercise has been reported as a positive regulator of skeletal muscle remodeling and apoptosis, however, as aforementioned, obese individuals typically present with low levels of physical activity (115). Interestingly, it has been suggested that the impaired function of mitochondria with obesity may be triggered by altering the expression of mitochondrial proteins regulating key metabolic processes in skeletal muscle likely due, in-part, to the subcellular localization of lipid droplets and a reduction in the amount of skeletal muscle perilipin 2 protein per intramyocellular lipid, particularly in type II muscle fibers (116,117).…”
Section: Implications Of Obesity For Aging Muscle Obesity and Musclementioning
confidence: 99%
“…The levels of mitochondrial fusion factors, mitofusin 2 (Mfn2) and porin, as well as citrate synthase activity, were lower in HF patients than those in age-matched healthy control subjects [ 91 ]. However, mitochondrial dysfunction may be partially normalized by exercise training in HF [ 83 , 92 ]. Our group showed that acute AET-induced upregulation of PGC-1 levels regulated the signaling pathway modulating mitochondrial biogenesis and protected muscles from oxidative stress, proteolysis, and inflammation [ 93 ].…”
Section: Effects Of Exercise On Hf-related Sarcopeniamentioning
confidence: 99%
“…Over Adipocytes in skeletal muscle tissue are leading to premature tissue aging (2,3). Obesity in adulthood is a medical condition in which excess body fat has accumulated leading to reduced lower skeletal muscle mass and strength with potential implications for developing sarcopenic obesity increased health problems (4,(5)(6). We hypothesize that resveratrol treatment in male mice programmed by obesity-induced sarcopenia and aging-associated sarcopenia would prevent skeletal muscle atrophy and muscle mass decreases.…”
Section: Introductionmentioning
confidence: 97%